2020
DOI: 10.3390/socsci9110202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Drug Trafficking Gangs on Overdose Deaths in the Largest Narcotics Market in the Eastern United States

Abstract: Research has found that drug markets tend to cluster in space, potentially because of the profit that can be made when customers are drawn to areas with multiple suppliers. But few studies have examined how these clusters of drug markets—which have been termed “agglomeration economies”—may be related to accidental overdose deaths, and in particular, the spatial distribution of mortality from overdose. Focusing on a large neighborhood in Philadelphia, Pennsylvania, known for its open-air drug markets, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…A number of studies have documented how law enforcement disruptions to the local drug market can result in persons with a chemical dependency to the seized substances shifting to alternative dealers or using different substances [1,12,16,[32][33][34][35][36][37]. Drug users can have a longstanding and trusting relationship with a supplier which often comes with consistency of a product quality [1].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented how law enforcement disruptions to the local drug market can result in persons with a chemical dependency to the seized substances shifting to alternative dealers or using different substances [1,12,16,[32][33][34][35][36][37]. Drug users can have a longstanding and trusting relationship with a supplier which often comes with consistency of a product quality [1].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the number of drug offenses per parcel during the pre-COVID and COVID timeframes ( Pre-COVID Drug Offenses and COVID Drug Offenses, respectively) were collected from the sample city’s police department. Because “drug trafficking organizations/gangs” are a predictor of proximal drug overdoses ( Johnson et al, 2020 , p. 13), data obtained from the sample city’s police department was used to create two additional binary measures were created, including whether each parcel was a known drug house ( Drug House coded as “1,” non-drug house coded “0”) or housed at least one known gang members ( Gang Member residence coded as “1,” non-gang member residence “0”). Two measures were created to reflect risky environments, yet also locations that someone may be likely to report a mental health or overdose incident.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The pandemic has also impacted the U.S. economy, which has been linked to increased suicide rates ( Oyesanya, Lopez-Morinigo, & Dutta, 2015 ). Furthermore, the literature has identified that a strong relationship between concentrated disadvantage and deaths resulting from a drug overdose ( Johnson et al, 2020 ). As such, a measure reflecting Concentrated Poverty was included in analysis ( Massey, 2001 ).…”
Section: Independent Variablesmentioning
confidence: 99%
“…2 ) and Kensington (B) neighborhoods of the city. Both are focal areas for the homeless populations, with the latter recently referred to as “the largest open-air heroin market on the East Coast of the United States” (Johnson et al, 2020 : 3). Health-related policing calls are up to four times more frequent in the afternoon and evening compared to the early hours of the morning (Fig.…”
Section: Spatio-temporal Patternsmentioning
confidence: 99%